The Influence Of The Number Of Spark Plug Ground Electrodes And Octane Value On Single Cylinder Engine Performance - Jefri Haris Sudarmanto; Yuniarto Agus Winoko (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
Multi-electrode spark plugs are a type of spark plug that has two or more ground points on the electrodes which function to produce sparks for the combustion process in gasoline engines. The aim is to find out how much the biggest change in power, the biggest torque is and how big the change in minimum specific fuel consumption is when using multi-ground spark plugs and varying the octane value of the fuel. The engine performance testing method uses full valve opening to obtain data. Next, the data is presented in the form of a graphic table and analyzed using Microsoft Excel and Minitab. The independent variables are the number of spark plug electrode legs and the octane value of the fuel. The dependent variable is the power produced and minimum specific fuel consumption when using RON 90, 92 and 98 fuel. The engine speed control variable is 55000 to 9000. Power test results using X-Line spark plugs with RON 92 fuel produce the highest power among spark plugs . other. The highest power is 6.92 hp at 7000 rpm. Torque test results using RON 98 fuel show that the X-Line spark plug produces the highest torque among other spark plugs. The highest torque is 8.21 Nm at 5,500 rpm. The results of the specific fuel consumption test using RON 92 fuel, 3 foot ground spark plugs, produced the highest specific fuel consumption among other spark plugs . The lowest specific fuel consumption is 0.1308 kg/hPxhour at 9000 rpm.